Kegiatan Sosialisasi Terpadu PKM Efektivitas Iklan Sebagai Upaya Meningkatkan Brand Image Pada Soto Minang Roda - Hilda Mary; Indriyenni Indriyenni; Nila Pratiwi (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
Small and Medium Enterprises (SMEs) play a very important role for the Indonesian economy, including the economy of the city of Padang. Data from the Central Statistics Agency (BPS) shows that the percentage of the number of Small and Medium Enterprises (SMEs) compared to the total number of companies in 2010 was 99 percent, while the rest were large companies. In the same year the number of workers absorbed in this sector reached 97 percent of the total working workforce. Small and Medium Enterprises (SMEs) play a very important role for the Indonesian economy, including the economy of the city of Padang. Data from the Central Statistics Agency (BPS) shows that the percentage of the number of Small and Medium Enterprises (SMEs) compared to the total number of companies in 2010 was 99 percent, while the rest were large companies. In the same year the number of workers absorbed in this sector reached 97 percent of the total working force.